2023
DOI: 10.3390/ani13193066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breeds on the Content of Functional Nutrition in Eggs

Caiyun Jiang,
Ruochen Chen,
Xuefeng Shi
et al.

Abstract: The purpose of this study was to compare the differences in the content of functional nutrients in eggs, performance parameters, and egg quality parameters of different chicken breeds. In Trial 1, 150 41-week-old hens of each breed, including the Dwarf Layer, White Leghorn, Silky fowl, Beijing-you chicken, and Shouguang chicken, were randomly assigned to the control (CON) and 2.5% flaxseed oil (FSO) groups to compare the difference in n-3 polyunsaturated fatty acid (PUFA) content in eggs. The contents of α-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In recent years, the functional nutrition of eggs has attracted the attention of many researchers ( Kralik and Kralik, 2017 ; Alagawany et al, 2019 ; Grcevic et al, 2019 ; Liu et al, 2020 ; Lu et al, 2020 ). In our previous research, we found significant differences in n-3 PUFA content in eggs from different breeds after feeding flaxseed oil, including Dwarf Layer, White Leghorn, Silky fowl, Beijing-you, and Shouguang ( Jiang et al, 2023 ). The contents of α-linolenic acid ( ALA ) (212.45 mg/yolk), DHA (100.32 mg/ yolk), and total n-3 PUFA (320.59 mg/yolk) in eggs of Dwarf Layer are the highest among the 5 breeds ( Jiang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In recent years, the functional nutrition of eggs has attracted the attention of many researchers ( Kralik and Kralik, 2017 ; Alagawany et al, 2019 ; Grcevic et al, 2019 ; Liu et al, 2020 ; Lu et al, 2020 ). In our previous research, we found significant differences in n-3 PUFA content in eggs from different breeds after feeding flaxseed oil, including Dwarf Layer, White Leghorn, Silky fowl, Beijing-you, and Shouguang ( Jiang et al, 2023 ). The contents of α-linolenic acid ( ALA ) (212.45 mg/yolk), DHA (100.32 mg/ yolk), and total n-3 PUFA (320.59 mg/yolk) in eggs of Dwarf Layer are the highest among the 5 breeds ( Jiang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 94%
“…In our previous research, we found significant differences in n-3 PUFA content in eggs from different breeds after feeding flaxseed oil, including Dwarf Layer, White Leghorn, Silky fowl, Beijing-you, and Shouguang ( Jiang et al, 2023 ). The contents of α-linolenic acid ( ALA ) (212.45 mg/yolk), DHA (100.32 mg/ yolk), and total n-3 PUFA (320.59 mg/yolk) in eggs of Dwarf Layer are the highest among the 5 breeds ( Jiang et al, 2023 ). In a study on broiler chickens, it was also found that there were significant differences in the contents of saturated fatty acid ( SFA ), monounsaturated fatty acid ( MUFA ) and n-3 PUFA in the muscles of different chickens breeds ( Cömert et al, 2016 ).…”
Section: Introductionmentioning
confidence: 94%
“…With the improvement of living standards and the popularization of dietary and nutritional knowledge, consumers are paying more attention to the relation between dietary structure and health and have higher expectations for egg quality ( Li et al, 2022 ; Jiang et al, 2023 ). Price, sensory attributes, and nutritional value all influence consumers’ purchasing intentions ( Chen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%